Essays on the Great Depression - Bernanke, Ben (Princeton University Press, 2000)
Few periods in history compare to the Great Depression. Stock market crashes, bread lines, bank runs, and wild currency speculation were worldwide phenomena--all occurring with war looming in the background. This period has provided economists with a marvelous laboratory for studying the links between economic policies and institutions and economic performance. Here, Ben Bernanke has gathered together his essays on why the Great Depression was so devastating. This broad view shows us that while the Great Depression was an unparalleled disaster, some economies pulled up faster than others, and some made an opportunity out of it. By comparing and contrasting the economic strategies and statistics of the world's nations as they struggled to survive economically, the fundamental lessons of macroeconomics stand out in bold relief against a background of immense human suffering. The essays in this volume present a uniquely coherent view of the economic causes and worldwide propagation of the Depression.